2013
DOI: 10.1111/geb.12112
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intraspecific competition on the distribution of a wide‐ranging, non‐territorial carnivore

Abstract: Aim It is generally held that the dominant competitors in a population will occupy high‐quality habitat while forcing subordinates into lower‐quality habitats through interference competition. We examined the distribution of a non‐territorial apex carnivore relative to foraging habitat to assess the effect of two types of interference: competitive asymmetries in predatory ability and conspecific predation risk. Location Beaufort Sea, Canada. Methods The quality of foraging habitat was modelled using resource s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
70
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 62 publications
(89 reference statements)
9
70
1
Order By: Relevance
“…In spring, subadults select for active ice that is near areas of open water (Stirling et al , Pilfold et al ), which may increase the need for short‐distance swims. Stirling () observed subadults swimming more frequently than other age‐classes in summer in the High Arctic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In spring, subadults select for active ice that is near areas of open water (Stirling et al , Pilfold et al ), which may increase the need for short‐distance swims. Stirling () observed subadults swimming more frequently than other age‐classes in summer in the High Arctic.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that prolonged exposure to frigid water may have negative consequences for offspring survival (Blix and Lentfer , Durner et al , Pagano et al ). Females with offspring‐of‐the‐year avoid habitats with open water in spring (Stirling et al , Freitas et al , Pilfold et al ) and may swim with cubs on their back to reduce offspring immersion (Aars and Plumb ). Reducing the frequency of swims is likely the main mechanism adult females use to protect their offspring from the high energetic cost associated with submergence in water.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Amundsen Gulf and Sanikiluaq during winter, ringed seals were resident in areas of stable shore-fast ice. Shore-fast ice with adequate snow cover allows ringed seals to minimise risk of predation by polar bears, who prefer to forage in areas of active sea ice further away from shore (Smith & Hammill 1981, Pilfold et al 2014. During winter at one of the most southern sampling locations (i.e.…”
Section: Resident Behaviour Relative To the Environmentmentioning
confidence: 99%